2021
DOI: 10.1111/basr.12220
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Redistribution of economic resources in the digital society

Abstract: The aftermath of the pandemic has sparked a deep global economic downturn and a significant rethinking of business technology. Digital transformation processes have intensified, which is reflected in the development of global supply chains. The purpose of this study is to conduct a descriptive comparative analysis of the processes of redistribution of economic resources and assess the processes of digital transformation of society and integration into world supply chains on the example of Russia. This study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Countries that digitise their production and economic activities can gain substantial economic benefits, also, through the example of Russia. Lomakina et al [52] argue that economic resources in the digital society will be transformed: the role of natural resources will be reduced, the development of renewable resources will be emphasised, and human resources, knowledge, and entrepreneurship will be valued. The finding of Szőllősi et al [53] at the company level indicate that a significant improvement can be achieved in profitability, competitiveness, and reducing negative environmental impacts through the complex application of state-of-the-art technologies, automation, robotics, and digitisation, as well as the necessary expertise acceptable at the national economy level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Countries that digitise their production and economic activities can gain substantial economic benefits, also, through the example of Russia. Lomakina et al [52] argue that economic resources in the digital society will be transformed: the role of natural resources will be reduced, the development of renewable resources will be emphasised, and human resources, knowledge, and entrepreneurship will be valued. The finding of Szőllősi et al [53] at the company level indicate that a significant improvement can be achieved in profitability, competitiveness, and reducing negative environmental impacts through the complex application of state-of-the-art technologies, automation, robotics, and digitisation, as well as the necessary expertise acceptable at the national economy level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of a study examining GDP output show that using DESI as an independent variable confirms the conclusion that digitalization positively influences economic growth [37]. The results of model studies showed that digitalization in the member states of the European Union has a positive effect [53][54][55][56][57] on competition, productivity, and output.…”
Section: Discussionmentioning
confidence: 61%
“…The obtained results indicate that innovative and new economies and enterprises develop at an accelerated pace in the EECCA region [30,31]. At the same time, the difficulties in achieving possible effects at the proper level of internationalization necessitate investments and funding for organizations in this field [32].…”
Section: Discussionmentioning
confidence: 86%